An energy aware hybrid firefly multipath distance vector protocol for efficient routing - Seetaram, J.; Satish Kumar, P. (International Journal of Engineering and Technology, 2019)
Mobile Ad Hoc Network (MANET) represents a system of wireless mobile nodes which move freely and also dynamically organizes as network with no pre-existing communication infrastructure. Owing to the traits like the temporary topology along with the absence of a centralized authority a major issue is the routing in the ad hoc networks. This work will evaluate the performance of that of an on-demand multipath routing protocol called Ad hoc On-demand Multipath Distance Vector (AOMDV) routing and also propose a new scheme of multipath routing employing the Fire Fly (FF) algorithm along with the Simulated Annealing (SA) approach. The proposed hybrid FF-SA scheme of routing is effective in finding an optimal solution for the MANET routing problem. The experimental results have proved that this method has achieved better performance.Â Â